Studi Komunikasi Geguritan Dharma Prawerti Dalam Meningkatkan Karakter Pemuda Desa Adat Runuh Kecamatan Buleleng Kabupaten Buleleng - Sumerta, Wayan; Despitasari, Ni Wayan Putri (Prabha Vidya, 2024)
Geguritan is one of the traditional Balinese literary works which is still alive and well developed. As something of high value, noble which has a very important meaning and meaning for people's lives. Geguritan comes from the word gurit, which means composition, coral, or sadur (Compiler Team, 2009: 251). Geguritan is a form of Traditional Balinese Literature which can be classified into prose form. The process of creating geguritan is not only in the past but the creation of geguritan is still alive and well today with various themes such as heroism and romance. Geguritan contains values that many people use as moral guidance. The research was conducted using qualitative methods, collecting primary data through interviews with purposive sampling techniques. The results showed that Geguritan Dharma Prawertti functions to improve the quality of the yowana in the Runuh Traditional Village community, namely starting to practice diligently, adding insight, changing behavior to be more polite in speech and actions.